Casing Prototype Design for Portable Electromagnetic Radiation Detector using 3D Printing Technology - Azman, Muhammad Akmal Hanif; Hassan, Mohd Fahrul; Sapuan, Syarfa Zahirah; Yee, See Khee (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Electromagnetic (EM) radiation comprises both natural and man-made radiation, which can be intentionally produced or arise as by-products. This radiation is transmitted through wired and wireless transmitters/receivers, electrical and electronic devices, and systems. Radio Frequency (RF) fields or EM fields have the capacity to cause heating in the human body when exposed to them, making them highly susceptible to this effect. The radiation detector that can fulfil the current demand and limitation by the existing product is worth to be developed with a local expert and users. Based on the previous study where the radiation detector was successfully designed. However, before being ready for up-scaling and mass production for the whole system, there is a need to design and develop a prototype to accommodate this device. Hence, the aim of this research is to design and develop casing prototype for portable radiation detector that be able to withstand outdoor environments conditions without interfering radiation measurements. The findings of this research indicate that the development of this casing prototype that be able to allow radiation penetration of EM fields with shielding effectiveness shows as low as 7 dB at the range operating frequencies. Other than that, development of casing prototype that can withstand outdoor environments also is possible with 3D printing technology as the casing tested to be able to resist water ingression and long-term UV exposure. Thus, it has been demonstrated that casing prototype design for portable radiation detector has been successfully developed to be use in real world application and ready for market.